Drug Eruption Due to Antituberculosis Drugs: A Case Report - Afida, Adinda Izzatul; Widiatma, Ridha Ramadina (NUTRIX, 2025)
Drug eruptions due to anti-tuberculosis drugs (ATDs) can compromise treatment adherence and outcomes. Identifying the culprit drug within combination regimens is particularly challenging, especially in patients with comorbidities that may increase susceptibility to cutaneous adverse reactions. We report a case of pulmonary tuberculosis with diabetes mellitus and hypertension who developed a generalized drug eruption after two months of ATD therapy. Clinical data, laboratory findings, management, and follow-up were evaluated descriptively. A 67-year-old male developed a generalized pruritic maculopapular eruption with edema after two months of fixed-dose ATD therapy. Laboratory tests showed no systemic involvement. The regimen was modified by continuing isoniazid and ethambutol while discontinuing rifampicin and pyrazinamide. Supportive therapy with a short course of systemic corticosteroids, antihistamines, and topical agents led to marked improvement within one week. The cautious use of systemic corticosteroids in a tuberculosis patient with comorbidities facilitated rapid resolution without clinical deterioration. This case highlights the need for individualized management of ATD-induced drug eruptions in patients with comorbidities. Selective continuation of isoniazid and ethambutol, withdrawal of rifampicin and pyrazinamide, and careful corticosteroid use proved both effective and safe. This report adds to the limited clinical evidence on managing drug eruptions in high-risk TB patients. Erupsi obat akibat obat anti-tuberkulosis (OAT) merupakan efek samping yang dapat mengganggu keberhasilan terapi. Tantangan terbesar adalah menentukan obat penyebab di tengah terapi kombinasi, khususnya pada pasien dengan komorbid yang dapat memperberat risiko reaksi kulit. Dilaporkan laporan kasus seorang pasien TB paru dengan komorbid diabetes mellitus dan hipertensi yang mengalami erupsi kulit setelah dua bulan terapi OAT. Data klinis, pemeriksaan penunjang, serta tindak lanjut terapi dievaluasi secara deskriptif. Seorang pria 67 tahun mengalami erupsi makulopapular generalisata dengan pruritus dan edema setelah dua bulan terapi OAT kombinasi. Pemeriksaan laboratorium tidak menunjukkan keterlibatan sistemik. Regimen dimodifikasi dengan melanjutkan isoniazid dan etambutol serta menghentikan rifampisin dan pirazinamid. Terapi suportif berupa kortikosteroid sistemik jangka pendek, antihistamin, dan agen topikal menghasilkan perbaikan signifikan dalam satu minggu. Keputusan penggunaan kortikosteroid pada pasien TB dengan komorbid berhasil mempercepat resolusi gejala tanpa memperburuk kondisi dasar. Kasus ini menyoroti pentingnya pendekatan individual dalam menatalaksana erupsi obat akibat OAT, khususnya pada pasien dengan komorbiditas. Strategi selektif melanjutkan isoniazid dan etambutol sambil menghentikan rifampisin dan pirazinamid, ditambah penggunaan kortikosteroid secara hati-hati, terbukti efektif dan aman. Laporan ini menambah bukti klinis mengenai tata laksana erupsi obat pada pasien TB dengan risiko tinggi.